Spring-seeded winter rye living mulches enhance crop biodiversity and promote reduced tillage organic soybeans - Brockmueller, Ben; Tautges, Nicole E.; Vereecke, Léa; Silva, Erin M. (Frontiers in Sustainable Food Systems, 2022)
As recognition increases of the benefits of reducing soil disturbance to preserve soil health, there is mounting interest in developing innovative methods of using cover crops as living mulches to control weeds in organic grain systems. Spring-planted winter cereal rye (Secale cereale L.) interseeded with soybeans (Glycine max. [L.] Merr.) is a promising, yet untested, living mulch system because rye exhibits vigorous growth in the early spring during the critical weed free period, but then dies back as the soybean canopy matures. The objectives of this study were to compare a rye living mulch system with a tilled “organic business-as-usual” control, and to understand the risks and benefits associated with delaying soybean planting date to manage the weed seed bank prior to establishment of rye and soybeans. Three treatments including (1) a June-planted rye and soybean living mulch system, (2) a June planted tilled control, and (3) a May planted tilled control, were compared in terms of weed prevalence and soybean grain yield in a randomized complete block experimental design with four replications implemented across 3 site years from 2019 to 2020. Interseeding rye as a living mulch resulted in consistently higher weed pressure as compared to tilled controls. Increased weed pressure in May- over June-planted controls in 2 of 3 site years indicate planting date influences weed dynamics. Rye biomass was positively correlated with soybean yield (R2 = 0.76, r = 0.87, p < 0.05) and negatively correlated with weed biomass (R2 = 0.63, r = −0.79, p < 0.05). Under optimal conditions where rye biomass was maximized, interseeding rye adequately suppressed weeds without reducing soybean yields as compared to tilled controls. However, under drier conditions with lower rye production, increased weed pressure and reduced yields emphasize the risks associated with living mulch systems.